The summation above can be expressed as where are integers.
Find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There is slight error in the question, we wanted to split the sum as n = − 1 ∑ ∞ ( n / 2 ) ! 1 = ( − 1 / 2 ) ! 1 + n = 0 ∑ ∞ ( n / 2 ) ! 1 = π 1 + e + e E r f ( 1 )